2004
DOI: 10.1111/j.1745-6584.2004.tb02621.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonization by Aerobic Bacteria in Karst: Laboratory and In Situ Experiments

Abstract: Experiments were carried out to investigate the potential for bacterial colonization of different substrates in karst aquifers and the nature of the colonizing bacteria. Laboratory batch experiments were performed using limestone and PVC as substrates, a natural bacterial isolate and a known laboratory strain (Escherichia coli [E. coli]) as inocula, and karst ground water and a synthetic formula as growth media. In parallel, fragments of limestone and granite were submerged in boreholes penetrating two karst a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Experimental data have demonstrated that biofilm-coated limestone can effectively adsorb the microspheres employed in the field experiment, while having a negligible influence on suspended R. eutropha concentrations. The presence of comparable biofilms along flow paths employed by tracers in the epikarst is likely (Personné et al 2004;Castegnier et al 2006), and may thus explain the contrast in R. eutropha and fluorescent microsphere tracer responses.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental data have demonstrated that biofilm-coated limestone can effectively adsorb the microspheres employed in the field experiment, while having a negligible influence on suspended R. eutropha concentrations. The presence of comparable biofilms along flow paths employed by tracers in the epikarst is likely (Personné et al 2004;Castegnier et al 2006), and may thus explain the contrast in R. eutropha and fluorescent microsphere tracer responses.…”
Section: Discussionmentioning
confidence: 99%
“…Although large areas of the world are influenced by karst and important processes such as groundwater recourse formation depend on the karst environment (Manda and Gross, 2006; Ford and Williams, 2007), little is known about microbial community composition and heterotrophic processes in these habitats. While research on springs and boreholes can give us a first idea about the diversity and function of microbial assemblages in karst environments (Personne et al. , 2004; Pronk et al.…”
Section: Introductionmentioning
confidence: 99%
“…A relative predominance of finer particles, for example, suggests an allochthonous origin and is often associated with faecal indicator bacteria contamination (Pronk et al 2007). Personné et al (2004) have studied bacterial colonisation of introduced substrates in a karst aquifer and concluded that enteric bacteria from periodical contamination with waste water were unlikely to persist in the system. Rusterholtz and Mallory (1994) have further described the bacterial community from Mammoth Cave (Kentucky, USA) sediments as highly diverse with no dominant species.…”
Section: Introductionmentioning
confidence: 99%